Single-dose combination nanovaccine induces both rapid and durable humoral immunity and toxin neutralizing antibody responses against Bacillus anthracis. Issue 29 (29th June 2021) - Kelly, Sean M.; Larsen, Kristina R.; Darling, Ross; Petersen, Andrew C.; Bellaire, Bryan H.; Wannemuehler, Michael J.; Narasimhan, Balaji
Highlights: Combining CDNs and polyanhydride nanovaccine induced rapid anti-PA IgG antibody titers. Combination nanovaccine enhanced serum neutralizing anti-PA IgG antibodies by 15 DPI. Vaccinated mice had low overall serum IgG responses to PA linear peptide epitopes. Combination nanovaccine induced anti-PA IgG-secreting cells in bone marrow and spleen. Abstract: Bacillus anthracis, the causative agent of anthrax, continues to be a prominent biological warfare and bioterrorism threat. Vaccination is likely to remain the most effective and user-friendly public health measure to counter this threat in the foreseeable future. The commercially available AVA BioThrax vaccine has a number of shortcomings where improvement would lead to a more practical and effective vaccine for use in the case of an exposure event. Identification of more effective adjuvants and novel delivery platforms is necessary to improve not only the effectiveness of the anthrax vaccine, but also enhance its shelf stability and ease-of-use. Polyanhydride particles have proven to be an effective platform at adjuvanting the vaccine-associated adaptive immune response as well as enhancing stability of encapsulated antigens. Another class of adjuvants, the STING pathway-targeting cyclic dinucleotides, have proven to be uniquely effective at inducing a beneficial inflammatory response that leads to the rapid induction of high titer antibodies post-vaccination capable of providing protection against bacterial pathogens. In this work, we evaluate the individual contributions of cyclic di-GMP (CDG), polyanhydride nanoparticles, and a combination thereof towards inducing neutralizing antibody (nAb) against the secreted protective antigen (PA) from B. anthracis . Our results show that the combination nanovaccine elicited rapid, high titer, and neutralizing IgG anti-PA antibody following single dose immunization that persisted for at least 108 DPI.